2020
DOI: 10.1016/j.mtla.2019.100522
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tensile yield strength in laser additively manufactured Al0.3CoCrFeNi high entropy alloy

Abstract: A precipitation strengthenable high entropy alloy (HEA), Al 0.3 CoCrFeNi, was processed via laser-based additive manufacturing (AM), using the laser engineered net shaping (LENS) process. The as LENS processed HEA exhibited twice the tensile yield strength, as compared to the conventionally arc-melted and solution treated HEA of the same composition, with a tensile ductility greater than 20%. Subsequent heat-treatments of the AM HEA alloy led to further enhancement of the yield strength while maintaining good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“… The effect of different AM technologies on tensile strength of Al 0.3 CrFeCoNi HEA in terms of YS, UTS and elongation. L-PBF [ 53 , 105 ], L-DED [ 145 , 146 ], AMF [ 247 , 248 ]. …”
Section: Figurementioning
confidence: 99%
“… The effect of different AM technologies on tensile strength of Al 0.3 CrFeCoNi HEA in terms of YS, UTS and elongation. L-PBF [ 53 , 105 ], L-DED [ 145 , 146 ], AMF [ 247 , 248 ]. …”
Section: Figurementioning
confidence: 99%
“…Additionally, DED has some advantages for the fabrication of bulk MPEA components. These advantages derive from the powder/ wire feed systems that enable changes in composition during the DED process across different layers which provides significant potential for fabricating functionally graded MPEA components with tailorable compositions, microstructures, and properties [73][74][75][76][77]. Without the manufacturing size limitation of the PBF, DED is reported to be able to fabricate large MPEA components (e.g., up to 5000 9 3000 9 1000 mm 3 ) with a high deposition rate (up to 300 cm 3 /h) [36,78].…”
Section: Directed Energy Deposition (Ded)mentioning
confidence: 99%
“…This indicated that CALPHAD based models were useful for predicting the phases formed in HEAs with complex components, but that the current thermodynamic database needs to be improved. Nartu et al (2020) investigated the effect of heat treatment on the microstructural evolution and mechanical properties of laser additively manufactured Al 0.3 CrFeCoNi HEA. The formation of the nano-scaled (Al, Ni)-rich clusters resulted from in-situ heat treatment during the part building and could act as the heterogeneous nucleation sites for the precipitates that form at high temperature aging.…”
Section: Thermodynamic Ways Of Annealingmentioning
confidence: 99%